(Nparadigma o(B. (Np(B. (Nkor{unowas (NsTATXQ PERWAQ(B. (NpONQTIE BIBLIOGRAFI^ESKOJ PARADIGMYs - (Nsokolow(B,(Na(B. (Nw(B.s (2014)
(Nw PERWOJ STATXE RASKRYTA OB]ENAU^NAQ TRAKTOWKA PONQTIJ (B"(NPARADIGMA(B", "(NOTRASLEWAQ PARADIGMA(B" (NI (B"(NBIBLIOGRAFOWED^ESKAQ PARADIGMA(B".s
Keywords: (Nkor{unow o(B. (Np(B.s -- (NBIBLIOGRAFs -- 1926-2013